Ответ:
AB: y = 1; BC: x = 2; AC: y = -x - 3
Пошаговое объяснение:
AB:
y=1" alt="\dfrac{x+4}{2+4} =\dfrac{y-1}{1-1} =>y=1" align="absmiddle" class="latex-formula">
BC:
x=2" alt="\dfrac{x-2}{2-2} =\dfrac{y-1}{-5-1} =>x=2" align="absmiddle" class="latex-formula">
AC: ![\dfrac{x+4}{2+4} =\dfrac{y-1}{-5-1} \\\\y-1 = -x-4\\\\y = -x - 3 \dfrac{x+4}{2+4} =\dfrac{y-1}{-5-1} \\\\y-1 = -x-4\\\\y = -x - 3](https://tex.z-dn.net/?f=%5Cdfrac%7Bx%2B4%7D%7B2%2B4%7D%20%3D%5Cdfrac%7By-1%7D%7B-5-1%7D%20%5C%5C%5C%5Cy-1%20%3D%20-x-4%5C%5C%5C%5Cy%20%3D%20-x%20-%203)